Transformasi Akad Natural Uncertainty Contracts: Analisis Akad Musyarakah Mutanaqishah (MMQ) di Lembaga Keuangan Syariah - Nurjaman, Muhamad Izazi; Sofie, Helmi Muti; Istianah, Istianah (TAWAZUN: Journal of Sharia Economic Law, 2022)
This research is motivated by the murabahah contract which is widely used by LKS in product development due to its nature which includes natural certainty contracts. So that it provides income certainty and has a lower risk than cooperation contracts (musyarakah and mudharabah) which are natural uncertainty contracts. However, in its development there is a musyarakah mutanaqishah contract which is a hybrid contract by combining musyarakah, ijarah and buying and selling contracts. Meanwhile, ijarah and buying and selling contracts are natural certainty contracts. This research will reveal the transformation of natural uncertainty contracts on the analysis of musyarakah mutanaqishah contracts in LKS. This study uses a normative juridical approach which is described by a descriptive method of literature from primary data sources and also secondary data. The type of this research is qualitative research with data analysis techniques in the form of focusing data, presenting data and drawing conclusions. The results of this study reveal the fact that there is a transformation of musyarakah contracts, which include natural uncertainty contracts, into musyarakah mutanaqishah contracts, which are hybrid contracts with business activities using ijarah contracts and buying and selling as natural certainty contracts. So that this contract provides income certainty and has low risk and can be used as a contract choice by LKS in developing financing products.